Utilization of watermelon (Citrullus lanatus) rinds as a natural low-cost biosorbent for adsorption of methylene blue: kinetic, equilibrium and thermodynamic studies. Issue 4 (4th July 2018) - Jawad, Ali H.; Ngoh, Y. S.; Radzun, Khairul Adzfa
ABSTRACT: This work presents the viability of biomass waste watermelon ( Citrullus lanatus ) rinds (WMR) as low-cost adsorbent for the removal of methylene blue (MB) from aqueous solution. The physicochemical properties of WMR were characterized using instrumental analyses such as CHNS-O analyzer, Brunauer-Emmett-Teller (BET), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and point of zero charge (pHpzc) analysis. The kinetic data revealed that the present system obeyed pseudo-second-order kinetic model. The equilibrium data were found to better fit with the Langmuir isotherm model than the Freundlich model. The adsorption capacity of WMR for MB was 188.68 mg/g at 303 K. The thermodynamic adsorption parameters, namely standard enthalpy ( H °), standard entropy ( S °) and standard free energy ( G °) showed that the adsorption of MB onto WMR was spontaneous and exothermic under the experimented conditions. These results indicate that the WMR can be feasibly employed for the eradication of MB from aqueous solution.